Psychopathology and languishing are distinct - Jayawickreme, Eranda; Blackie, Laura E.R. (Taylor & Francis, 2017)
Halls-Simmons and McGrath have proposed that character strengths can moderate the impact that clinical symptoms have on functioning. This notion is reasonable in light of existing evidence. Specifically, we provide secondary analyses from data first presented in Blackie, Jayawickreme, Forgeard, & Jayawickreme (2015) suggesting that character strengths can moderate the impact of psychopathology on functioning. We argue however that this conceptual work should only the first step in developing a comprehensive model of how flourishing can be promoted and languishing avoided.